Contextualising Translator Training: Defining Social, Professional and Disciplinary Requirements - Plaza-Lara, Cristina (De Gruyter, 2016)
In order to adapt universities to the social, disciplinary and professional needs, we consider it necessary to contextualise the professional profiles of translators. The main groups involved in the educational process are translation teachers and researchers, employers and students/graduates, and their contribution to the definition of professional profiles is essential. Therefore, in this article we will focus on studies about professional profiles from the following perspectives: translation market studies, academic research, research on labour market insertion and students’ expectations. These studies will allow us to draw conclusions that could be applied during curricular design.
Keywords: Traductores - Formación profesional; Perfiles profesionales en traducción; Formación de traductores; Requisitos sociales, disciplinarios y profesionales; Versatilidad en la formación de traductores